RNA Sequencing Keloid Transcriptome Associates Keloids With Th2, Th1, Th17/Th22, and JAK3-Skewing - Wu, Jianni; Del Duca, Ester; Espino, Michael; Gontzes, Alyssa; Cueto, Inna; Zhang, Ning; Estrada, Yeriel D.; Pavel, Ana B.; Krueger, James G.; Guttman-Yassky, Emma (Frontiers in Immunology, 2020)
Keloids are disfiguring, fibroproliferative growths and their pathogenesis remains unclear, inhibiting therapeutic development. Available treatment options have limited efficacy and harbor safety concerns. Thus, there is a great need to clarify keloid pathomechanisms that may lead to novel treatments. In this study, we aimed to elucidate the profile of lesional and non-lesional keloid skin compared to normal skin. We performed gene (RNAseq, qRT-PCR) and protein (immunohistochemistry) expression analyses on biopsy specimens obtained from lesional and non-lesional skin of African American (AA) keloid patients compared to healthy skin from AA controls. Fold-change ≥ 2 and false-discovery rate (FDR)<0.05 was used to define significance. We found that lesional versus normal skin showed significant up-regulation of markers of T-cell activation/migration (ICOS, CCR7), Th2- (IL-4R, CCL11, TNFSF4/OX40L), Th1- (CXCL9/CXCL10/CXCL11), Th17/Th22- (CCL20, S100As) pathways, and JAK/STAT-signaling (JAK3) (false-discovery rate [FDR]<0.05). Non-lesional skin also exhibited similar trends. We observed increased cellular infiltrates in keloid tissues, including T-cells, dendritic cells, mast cells, as well as greater IL-4ra+, CCR9+, and periostin+ immunostaining. In sum, comprehensive molecular profiling demonstrated that both lesional and non-lesional skin show significant immune alternations, and particularly Th2 and JAK3 expression. This advocates for the investigation of novel treatments targeting the Th2 axis and/or JAK/STAT-signaling in keloid patients.